Pengaruh Modal Kerja, Aset, Dan Omzet Penjualan Terhadap Laba Ukm Catering Di Wilayah Surakarta - SUPRIHATMI SRI WARDININGSIH (Jurnal Perilaku dan Strategi Bisnis, 2017)
This study aimed to determine the effect of working capital, asset, and sales turnover to profits of SMEs. The population in this study is catering SMEs (Small and Medium Enterprises) at Surakarta located in the five districts. The sample in this study are catering SMEs in Surakarta consist of 92 SMEs. The data in this study using secondary data from the quarterly financial statements of catering SMEs in Surakarta on 2015 that fully include working capital, fixed assets, sales turnover and profit. Result of this research show that working capital have positive and significant effect on SMEs profits, means Hypothesis 1 is accepted. Assets no significant effect on SMEs profit means Hypothesis 2 was rejected. Sales turnover have positive and significant effect on SMEs profit means Hypothesis 3 is accepted. Implications of this research, increase in working capital and sales turnover have a positive contribution on profits of SMEs catering in Surakarta.